When banks' shadow fades and shadow banking rises: Securitization and loan performance in China - Di Gong; Jin Wu; Jigao Zhu (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
This study examines the relationship between securitization and loan performance using proprietary loan-level data from a Chinese bank. Securitized loans exhibit lower ex-post default rates and prepayment chances compared to the loans retained on the bank's balance sheet, suggesting no adverse selection or moral hazard within the Chinese securitization market. Our finding is robust to controlling for possible endogeneity of loan selection by employing propensity score matching and instrumental variable estimators. Exploiting the introduction of the New Asset Management Rule as a quasi-natural experiment, which alters banks' business model and eliminates other options of credit risk transfer except for securitization, we show worse loan performance after the new regulation, in line with deterioration of the bank's incentive. This unintended consequence of the New Asset Management Rule, aimed at curbing shadow banking activities of banks, highlights the emergence of risk in the securitization sector of the shadow banking.
Keywords: G21; D82; 330; Securitization; loan performance; adverse selection; moral hazard; information frictions; default risk; prepayment risk